Genomic Analysis of the 1-Aminocyclopropane-1-Carboxylate Deaminase-Producing Pseudomonas thivervalensis SC5 Reveals Its Multifaceted Roles in Soil and in Beneficial Interactions With Plants - Nascimento, Francisco X.; Urón, Paola; Glick, Bernard R.; Giachini, Admir; Rossi, Márcio J. (Frontiers in Microbiology, 2021)
Beneficial 1-aminocyclopropane-1-carboxylate (ACC) deaminase-producing bacteria promote plant growth and stress resistance, constituting a sustainable alternative to the excessive use of chemicals in agriculture. In this work, the increased plant growth promotion activity of the ACC deaminase-producing Pseudomonas thivervalensis SC5, its ability to limit the growth of phytopathogens, and the genomics behind these important properties are described in detail. P. thivervalensis SC5 displayed several active plant growth promotion traits and significantly increased cucumber plant growth and resistance against salt stress (100 mmol/L NaCl) under greenhouse conditions. Strain SC5 also limited the in vitro growth of the pathogens Botrytis cinerea and P. syringae DC3000 indicating active biological control activities. Comprehensive analysis revealed that P. thivervalensis SC5 genome is rich in genetic elements involved in nutrient acquisition (N, P, S, Fe); osmotic stress tolerance (e.g., glycine-betaine, trehalose, ectoine biosynthesis); motility, chemotaxis and attachment to plant tissues; root exudate metabolism including the modulation of plant phenolics (e.g. hydroxycinnamic acids), lignin, and flavonoids (e.g. quercetin); resistance against plant defenses (e.g. reactive oxygens species-ROS); plant hormone modulation (e.g., ethylene, auxins, cytokinins, salicylic acid), and bacterial and fungal phytopathogen antagonistic traits (e.g., 2,4-diacetylphloroglucinol, HCN, a fragin-like non ribosomal peptide, bacteriocins, a lantipeptide, and quorum-quenching activities), bringing detailed insights into the action of this versatile plant-growth-promoting bacterium. Ultimately, the combination of both increased plant growth promotion/protection and biological control abilities makes P. thivervalensis SC5 a prime candidate for its development as a biofertilizer/biostimulant/biocontrol product. The genomic analysis of this bacterium brings new insights into the functioning of Pseudomonas and their role in beneficial plant-microbe interactions.